2020
DOI: 10.3390/d12070278
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiome Metabarcoding in Two Invasive Small Mammals from New Zealand

Abstract: All multicellular organisms host a wide diversity of microorganisms in and on their bodies, which are collectively known as their microbiome. Characterising microbial communities that inhabit different body niches in wild animals is critical to better understand the dynamics of microbiome diversityand its functional significance. The current study is the first to apply massively parallel sequencing of 16S rRNA to characterise the microbial diversity and functional content of oral microbiota in two of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Functional aspects of the possum and stoat microbiomes are of particular research interest due to the potential microbial contribution towards the evolutionary success of these host species, distinct from host-specific genomic adaptations. With an eye to the potential future development of novel, microbiome-targeted biocontrols for these destructive mammal species, recent work has identified that the dominant bacterial phyla Proteobacteria, Firmicutes, Bacteroidetes, Fusobacteria, and Actinobacteria are characteristic core members of the brushtail possum and stoat oral cavities (Emami-Khoyi et al 2020), though continued work into microbial function should be pursued.…”
Section: Mammalsmentioning
confidence: 99%
“…Functional aspects of the possum and stoat microbiomes are of particular research interest due to the potential microbial contribution towards the evolutionary success of these host species, distinct from host-specific genomic adaptations. With an eye to the potential future development of novel, microbiome-targeted biocontrols for these destructive mammal species, recent work has identified that the dominant bacterial phyla Proteobacteria, Firmicutes, Bacteroidetes, Fusobacteria, and Actinobacteria are characteristic core members of the brushtail possum and stoat oral cavities (Emami-Khoyi et al 2020), though continued work into microbial function should be pursued.…”
Section: Mammalsmentioning
confidence: 99%
“…from the surface of the WaxTags ® , suggests that the same methodology can potentially be applied to test for the presence of Mycobacterium bovis and other pathogenic organisms that reside within the oral cavity. Some of the bacterial taxa from the surface of WaxTags ® are asymptotic inhabitants of the upper respiratory system and the oral cavity in mammals (Talan et al, 1999;Dewhirst et al, 2012;Cheng et al, 2015;Gomez et al, 2017;Emami-Khoyi et al, 2020), while others are environmental microorganisms that live ubiquitously in different terrestrial and aquatic habitats. In a subset of hosts with compromised immune system, these microorganisms can cause severe localised or systemic diseases, and infected individuals form new reservoirs to spread the infection.…”
Section: Partial Oral Microbiome Reconstructionmentioning
confidence: 99%